(untitled) (Globalization and Business, 2023)
In recent years, logistics have gained great importance both locally and internationally. The status of a "transit country" has long been an important precondition for the development of the economy and international relations of Georgia. With the growth of the economy, Georgia's function as a trans-Caucasian corridor has expanded. This is the shortest route connecting East Asia with the Europe. Significant railway, motorway, and pipeline transport passes through the territory of Georgia – by means of which, it is possible to cheaply and efficiently transport goods from the Caspian Sea to the Black Sea and vice versa. As a result of economic and infrastructural reforms carried out in recent years, the transport and logistics sector in Georgia has developed significantly, but not sufficiently yet. As a result of infrastructure modernization, simplification of customs procedures, and liberalization of services in key sectors of the economy, the country's transit and logistics potential has been increased, providing better international connections with global markets. Georgia is currently modernizing and expanding its transport infrastructure, which includes a growing national expressway system, new rail routes, international airports, and expanded seaports/terminals. At the same time, legislative approximation with the EU continues in the field of transport, which is a priority issue in the process of Georgia's European integration. The development of the country's infrastructure, transport, logistics, communications, energy, technology, education and financial hubs is important for realizing the potential. Donors are providing their assistance in achieving Georgia's logistics goals. With their help, the National Logistics Strategy of Georgia for 2021-2030 was prepared, which states that the logistics sector of Georgia is in the process of transformation. An important indicator of the state of the logistics sector in Georgia is the World Bank Logistics Index (LPI), where Georgia is not in the most favorable place (119th place among 160 countries). The Logistics Index reflects the vision of international service providers and business operators on how countries integrate into the global logistics network through their major trade gateways. Therefore, it reflects not only the changes throughout the country, but also problems associated with the access overseas. It should be noted that over the past decade Georgia has invested heavily in the development of road infrastructure, but logistics and intermodal infrastructure continues to be developed, resulting in low efficiency of maintenance of logistics system, relatively its high cost and less reliability of the logistics system, which negatively affects international transportation. COVID-19 has affected not only on the healthcare system, but also on global critical infrastructure, including transport and logistics. The start of the pandemic highlighted a critical importance of transport and logistics systems, both on international and local level, which previously had not gained much attention. Despite the success achieved, number of problems has remained for transformation of Georgia into a regional transit and logistics hub. Efforts to improve transport infrastructure and services should continue until existing constraints are completely removed. Poor service quality, outdated logistics infrastructure and equipment, ineffective supply chain management, as well as disorganization of personnel and their poor qualification are not a complete list of problems. An effective and consistent policy for the development of transport and logistics will make Georgia more attractive for investment and improve the country's economic potential.